THE ROLE OF AI IN LANGUAGE LEARNING - Mamatqulova Diyonat Shavkat qizi (TADQIQOTLAR, 2025)
Annotation. This article examines the growing role of  Artificial Intelligence (AI) in language learning, highlighting its transformative impact on both formal and informal educational contexts. It explores how AI-powered tools—such as language learning  apps,  chatbots,  personalized  learning  platforms,  and  machine  translation services—are reshaping the way learners acquire and interact with new languages. The study also discusses the benefits of AI, including adaptive learning, real-time feedback, and  immersive  language  environments,  while  addressing  challenges  such  as  over-reliance on technology, privacy concerns, and the potential loss of human interaction. Overall,  the  article  provides  a  comprehensive  overview  of  how  AI  is  enhancing language  acquisition  processes  and  contributing  to  more  accessible  and  efficient language education worldwide.